An Empirical Test of Racial/Ethnic Differences in Perceived Racism and Affiliation with the Gay Community: Implications for HIV Risk. (June 2014) - Haile, Rahwa; Rowell‐Cunsolo, Tawandra L.; Parker, Edith A.; Padilla, Mark B.; Hansen, Nathan B.; Rivera, Luis M.; Beatty Moody, Danielle L.
<x xml:space="preserve">Abstract</x> Studies of sexual stigma management techniques expected to decrease HIV risk among Black men who have sex with men (MSM) have yielded some counterintuitive findings. For example, some research suggests that identification with and participation in the gay community may be related to higher levels of sexual risk behavior among Black MSM. Moreover, some of this research tends to assume that Black and White MSM experience the gay community in identical ways. Borrowing from key tenets of intersectionality theory, we examine whether there are substantive differences in the ways in which Black and White MSM experience the gay community. In particular, we use the Urban Men's Health Study to quantitatively test Black–White differences in perceptions of racial hierarchy and racism within and positive affiliation with the gay community. Our findings suggest that Black MSM may encounter racism, and may experience engagement with the gay community as less positive than their White counterparts. These data contextualize existing research, and suggest that racism may shape the extent to which affiliation with the gay community serves as a protective factor against HIV for Black MSM.